2021
DOI: 10.3329/bjas.v50i1.55568
|View full text |Cite
|
Sign up to set email alerts
|

Forage growth, biomass yield and nutrient content of two different hybrid Napier cultivars grown in Bangladesh

Abstract: A 2×3 factorial experiment was conducted to compare two cultivars; Bangladesh Livestock Research Institute developed Napier hybrid-3 (BN-3) (Pennisetum purpureum) and Pakchong-1 (Pennisetum purpureum× P. glaucum) in terms of forage growth, biomass yield, and nutritional quality. Cultivars were cultivated in 03 blocks with 03 replicates and were harvested at 03 cutting periods (40, 50, and 60 days). Plot sizes for each cultivar were 25 m2 (5m × 5m), and in every plot, twenty-five stem cuttings with two healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…In this study, the CP value of the Packhong1 variety used was determined as 12.21%. In a study conducted by Ahamed et al (2021), the CP values of Packhong1 grasses were found to be between 9.49% and 11.23%. In another study, CP values of Packhong1 grasses were observed to be between 8.64% and 12.64% (Lounglawan et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…In this study, the CP value of the Packhong1 variety used was determined as 12.21%. In a study conducted by Ahamed et al (2021), the CP values of Packhong1 grasses were found to be between 9.49% and 11.23%. In another study, CP values of Packhong1 grasses were observed to be between 8.64% and 12.64% (Lounglawan et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…et al, 2017). Jumlah anakan dan tingkat daun yang lebih tinggi pada Pakchong 1 dihasilkan pada periode pemotongan 60 hari (Ahmed et al, 2021). Penggunaan kompos kotoran ternak ayam menghasilkan berat kering daun, batang dan tajuk tanaman rumput gajah cv.…”
Section: Metode Penelitianunclassified
“…Dari nilai berat kering daun dibandingkan dengan berat kering batang rumput gajah cv Pakchong dalam penelitian ini, mengindikasikan bahwa proporsi daun lebih banyak dibandingkan dengan proporsi batang. Kultivar gajah Pakchong 1 menghasilkan proporsi daun (0,23kg) yang lebih tinggi dibandingkan dengan proporsi batang (0,19kg) pada kultivar gajah lainnya (BN-3) (Ahmed et al, 2021). Sementara itu, persentase daun dan batang yang diperoleh pada penerapan pupuk kotoran ayam pada penanaman rumput Pennisetum purpureum cv.…”
Section: Metode Penelitianunclassified
“…Sakina et al (2019) menyebutkan bahwa tanaman telah mengandung hormon sitokinin yang cukup, sehingga membantu mempercepat pembelahan sel dalam pembentukan tunas baru. Pada penelitian sebelumnya (Ahmed et al 2021) melaporkan bahwa pada rumput gajah pakchong dengan interval pemotongan 40 hari memiliki jumlah anakan 24,6 per rumpun.…”
Section: Jumlah Anakan Dan Jumlah Daun Rumput Gajah Pakchongunclassified